The Strategies of Coping with Critical Life Situations Adopted by Businesswomen - T A Bergis (Peoples' Friendship University of Russia (RUDN University), 2011)
The article is devoted to studying the features of coping with critical situations adopted by businesswomen. The chosen coping strategies interrelated with personality characteristics, understanding the meanng of life, career orientations, life-course peculiarities of businesswomen are analyzed.